Synthesis of 6-hydroxyaurone analogues and evaluation of their α-glucosidase inhibitory and glucose consumption-promoting activity: Development of highly active 5, 6-disubstituted derivatives. Issue 15 (1st August 2017) - Sun, Hua; Ding, Weina; Song, Xiaotong; Wang, Dong; Chen, Mingzhu; Wang, Kaili; Zhang, Yazhou; Yuan, Peng; Ma, Ying; Wang, Runling; Dodd, Robert H.; Zhang, Yongmin; et al.
Graphical abstract: Abstract: A series of 6-hydroxyaurones and their analogues have been synthesized and evaluated for their in vitro α-glucosidase inhibitory and glucose consumption-promoting activity. These compounds exhibited varying degrees of α-glucosidase inhibitory activity, 11 of them showing higher potency than that of the control standard acarbose (IC50  = 50.30 μM). Surprisingly, analogues devoid of a substituent at C-2 but having an aryl group at C-5 were found to be highly active (e.g., 7f, IC50  = 9.88 μM). Docking analysis substantiated these findings. The kinetic analysis of compound7f, the most potent α-glucosidase inhibitor of this study, revealed that it inhibited α-glucosidase in an irreversible and mixed competitive mode. In addition, compounds7f and10c exhibited significant glucose consumption promoting activity at 1 μM.